Immigration and Housing Booms: Evidence from Spain - Libertad Gonzalez; Francesc Ortega (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
We estimate empirically the effect of immigration on house prices and residential construction activity in Spain over the period 1998-2008. This decade is characterized by both a spectacular housing market boom and a stunning immigration wave. We exploit the variation in immigration across Spanish provinces and construct an instrument based on the historical location patterns of immigrants by country of origin. The evidence points to a sizeable causal effect of immigration on both prices and quantities in the housing market. Between 1998 and 2008, the average Spanish province received an immigrant inflow equal to 17% of the initial working-age population. We estimate that this inflow increased house prices by about 52% and is responsible for 37% of the total construction of new housing units during the period. These figures imply that immigration can account for roughly one third of the housing boom, both in terms of prices and new construction.
Keywords: F22; J61; R21; R23; R31; 330; Housing market; Immigration; House prices; Construction; Spain